Correlation of Tp-e interval and Tp-e/Q-T ratio with malignant ventricular arrhythmia in patients with implantable cardioverter-defibrillator for primary prevention - Zhu, Ting-Yan; Teng, Shu-En; Chen, Yan-Yu; Liu, Shen-Rong; Meng, Su-Rong; Peng, Jian (Nan fang yi ke da xue xue bao = Journal of Southern Medical University, 2016)
To investigate whether Tpeak-Tend interval (Tp-e) and Tp-e/QT ratio are associated with malignant ventricular arrhythmia in patients with implantable cardioverter-defibrillator (ICD) for primary prevention. A cohort of 68 consecutive patients with chronic heart failure undergoing standard ICD for primary prevention indications (NYHA function class II-III, left ventricular ejection fraction ≤35%, systolic cardiomyopathy without prior malignant ventricular arrhythmia) were enrolled in this study. The patients were followed up for 18-48 months and were divided into high-risk group and low-risk group according to the occurrence of the endpoint events of sudden cardiac death (SCD), ventricular tachycardia (VT), or ventricular fibrillation (VF). Electrocardiographic and echocardiographic characteristics, Tp-e, and Tp-e/QT ratio were analyzed in all cases before ICD implantation. During the follow-up, ICD shock for sustained ventricular tachycardia or ventricular fibrillation occurred in 11 patients; nonsustained ve